ANALYZING PRESIDENTIAL COMMUNICATION: JOKOWI DODO’S USE OF DIALECT IN ANTI-CORRUPTION SPEECHES - Lisbeth Juliana Sidauruk; Novelliny Arishta Mutya; Christine Lumbantobing; Evelyn Metafati Zebua; Honey Crysty Marbun (Adisam Publisher, 2024)
This study analyzes President Joko Widodo’s (Jokowi) use of dialect in his anti-corruption speeches, focusing on its effectiveness in shaping public perception and mobilizing support. Utilizing Framing Theory, the research examines how Jokowi’s linguistic choices frame the anti-corruption narrative. The qualitative analysis of Jokowi’s World Anti-Corruption Day speech reveals that his use of local dialect and informal language fosters relatability and trust, bridging the gap between the government and the people. Findings indicate that Jokowi’s strategic framing of corruption as a collective moral responsibility and a common enemy mobilizes public support and reinforces a national identity centered on integrity and transparency. This approach effectively highlights both achievements and ongoing challenges in the fight against corruption, maintaining public engagement and trust. The study underscores the importance of strategic communication in political leadership and offers insights for enhancing anti-corruption campaigns in Indonesia.